Drag Force Simulation of Particle Agglomerates with the Lattice Boltzmann Method - Thürey, Nils; Rüde, Ulrich; Peukert, Wolfgang; Feichtinger, Christian; Binder, Christian; Schmid, Hans-Joachim (18th Symposium Simulationstechnique ASIM 2005 Proceedings, 2005)
In this work we show, that the Lattice Boltzmann method is capable of calculating the drag force on spheres with a sufficient accuracy. The main Interest lies on laminar flows around nano particle agglomerates. To give an overview over the simulated force accuracy the results are compared with analytical solutions. Thereby the benefit from curved boundary treatments such as [YD03] and [PL03] is taken into account. Through the use of curved boundary treatments the lattice radius of the spheres can be reduced and thus smaller domain sizes can be used with the same force accuracy. Further more, results for complex agglomerates are presented and compared to solutions of the Stokesian Dynamics approach [AS01]
UnivIS-Import:2015-04-16:Pub.2005.tech.IMMD.lsinfs.dragfo_7
Keywords: drag; stokkesian; simulation; lattice; boltzmann